Etika Wakil Rakyat dan Respon Publik terhadap Kebijakan Kontroversial: Refleksi atas Demonstrasi Agustus 2025 - Rhomadani Sinta Pratiwi; Ali Rokhman (Journal of Innovative and Creativity, 2025)
This study discusses the ethical practices of legislators and public responses to a controversial policy regarding the increase of housing allowances for members of the DPR, which triggered large scale demonstrations in August 2025. The policy was perceived by the public as inconsistent with the government’s mission of budget efficiency, leading to a wave of distrust. The purpose of this research is to analyze the ethical practices of legislators in policymaking, to examine public responses to the policy, to explore its implications for the quality of the relationship between citizens and their representatives, and to formulate strategies for improving the political ethics of legislators to ensure more transparent and accountable legislative processes. The research employed a descriptive qualitative method by analyzing literature, official documents, media reports, and digital data from social media. The data were critically analyzed to illustrate the dynamics of the relationship between legislators’ ethics and public responses to DPR’s controversial policies. The findings show that DPR’s ethical practices were primarily oriented toward internal organizational interests, while neglecting public sensitivities to socio-economic conditions. This led to public responses that escalated from peaceful criticism to anarchic demonstrations, accompanied by the “17+8 points” demands. Digital activism and the role of influencers further amplified public pressure, making this issue highly visible in the public sphere. The study concludes that the August 2025 demonstrations reflect a crisis of political ethics and the legitimacy of legislators. This crisis can only be addressed through ethical reforms that place citizens at the center of representation. Without serious reform, DPR risks further losing its social legitimacy.